1955
DOI: 10.1177/004051755502500801
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Scoured Wool

Abstract: The 6 inherent fiber properties, tensile strength, fiber length, fiber thickness, contour (major-minor axis), crimp length to depth ratio, and crimp depth were responsible for 31 % of the variations in the compressional-bulk resilience of wool. In the case of maximum load or stiffness, these same 6 inherent fiber properties were responsible for 85% of the variations. In both cases, the most important inherent property was tensile strength. It accounted for 17% of the variations in the compressional-bulk resili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1955
1955
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Van Wyk [50] claimed that the compression of fiber bundles would be independent of.fiber fineness and produced some results to support this theory. Demiruren and Burns [13] contested van Wyk's theory and gave evidence which clearly contradicted it. Hamilton [20] also demonstrated a relationship between fiber fineness and yarn density· Hoffman [24] discussed the ideal packing of uniforl11 rods and showed that, by mixing rods of differing diameter in certain instances, a great increase jn percent free space within the structure was achieved.…”
Section: Fiber Propertiesmentioning
confidence: 99%
“…Van Wyk [50] claimed that the compression of fiber bundles would be independent of.fiber fineness and produced some results to support this theory. Demiruren and Burns [13] contested van Wyk's theory and gave evidence which clearly contradicted it. Hamilton [20] also demonstrated a relationship between fiber fineness and yarn density· Hoffman [24] discussed the ideal packing of uniforl11 rods and showed that, by mixing rods of differing diameter in certain instances, a great increase jn percent free space within the structure was achieved.…”
Section: Fiber Propertiesmentioning
confidence: 99%
“…Investigations have previously been conducted in this tield by a number of research workers mostly on wool fibers, and these have been reviewed by Demiruren and Burns [1). Recently, Sebestyen and Hickie [2J have reported the effect of certain fiber properties on the compressibility of wool at medium and high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Early measurements were done, using systems with different cylinders and pistons. [24][25][26] However, when the Australian standard AS 3535-1988 was issued, a standard methodology was introduced and developed as the Commonwealth Scientific and Industrial Research Organization (CSIRO) compressibility tester (Figure 1 (a)). After it had been demonstrated that wool with greater RtC value generally has a harsher handle, 14,27 this instrument was used to grade the softness of Australian wool.…”
mentioning
confidence: 99%